The importance of prenatal follow-up in basic care in the vision of pregnant women (Research, Society and Development, 2023)
Introduction: Pregnancy is a unique experience in the life of a woman and her family, and throughout pregnancy physiological changes will occur, generating expectations, emotions, anxiety, fears and discoveries. In this period, therefore, it is necessary to offer adequate attention to the pregnant woman's health. Objectives: The objectives of this research were to know the pregnant women's view of the prenatal care provided in primary care; identify the possible reasons that lead pregnant women to abandon prenatal care; analyze the perceptions and knowledge of pregnant women about the importance of prenatal care and its benefits, and describe the sociodemographic profile of pregnant women. Methodology: This research is classified as qualitative, and counted on the participation of eight pregnant women who agreed to participate in the research. During the interview, questions were asked about pregnancy and prenatal care, in a format that they could answer openly, being able to expose their frustrations, doubts and anxieties. Results and Discussions: After transcribing the interviews, they were analyzed, and from that, four categories emerged: Category 1 - The care received by the nursing team during prenatal care and the satisfaction of pregnant women; Category 2 - The rights of pregnant women; Category 3 - Reasons that interfere with the success of prenatal care; Category 4 - Insecurities during pregnancy. Conclusion: Pregnant women care about prenatal care and seek information; some of them have already had negative experiences, so they pay extra attention to this moment.